FUNGAL-BASED INTERVENTION AGAINST TICK-BORNE PARASITIC THREATS IN CATTLE: FOCUS ON RHIPICEPHALUS MICROPLUS (The Research of Medical Science Review, 2025)
Ticks are a serious threat to both humans and animals, spreading diseases babesiosis anaplasmosis, theileriosis, borreliosis, Crimean-Congo haemorrhagic fever (CCHF) and Lyme disease globally including Pakistan. They also cause enormous financial losses, particularly in in Khyber Pakhtunkhwa Pakistan's livestock sector. Resistance and environmental issues make traditional chemical control approaches difficult to use. In order to investigate environmentally acceptable biopesticides, entomopathogenic fungus Beauveria bassiana and Metarhizium anisopliae that were isolated from soil and tested against Rhipicephalus microplus ticks were used. The results demonstrated that higher fungal concentrations increased ticks death, with the mixed fungus having a 96% efficacy at 10^9 conidia/mL. The LC50 values for B. bassiana and M. anisopliae were 1 x 10¹⁵ and 4.68 x 10¹⁶ conidia/mL, respectively, indicating significant pathogenicity. This entailed experimenting with various application methods, including as sprays, baits, and formulations, to improve efficacy while reducing environmental impact